NORMA KULTIVOVANÉ VÝSLOVNOSTI, JEJÍ POPIS A OSVOJOVÁNÍ - KRČMOVÁ, MARIE (Slavia Occidentalis, 2020)
The norm of received pronunciation and its description in the codification does not have a long tradition. Beside short remarks in grammars, several short individual works were written since the mid-19th century but they were usually not generally accepted. Although 75 years ago, general guidelines for the codification of the pronunciation in Czech were proposed, followed by the first publication 60 years ago, its practical implementation was difficult. It should have an impact on public speech but the articulation mechanism is fixed naturally since childhood, and the defects are hard to remove without motivation. What is more, pronunciation instructions are presented in a written form, and it is necessary to express them with the user – a layman – in mind. Still, endeavours should be made to understand and to codify the pronunciation norms.